A distinctive translocation carcinoma of the kidney ["rosette-like forming," t(6;11), HMB45-positive renal tumor] - Hora, Milan; Hes, Ondrej; Urge, Tomás; Eret, Viktor; Klecka, Jirí; Michal, Michal (International urology and nephrology, 2009)
OBJECTIVE: Recently, a novel renal carcinoma with specific clinical and histological characteristics and translocation t(6;11)(p21.1;q12 or q13) has been identified. We have found 11 cases in the literature, and we are adding another 3 cases. MATERIALS AND METHODS: Three cases were found in the Plzen pathological register with approximately 15,000 cases of kidney tumors. There were two females and 1 male, aged 22, 24, and 39 years. RESULTS: The sizes of the tumors were 40, 136, and 10 mm. Two tumors were found incidentally; the biggest one was self-palpated by a 24-year-old pregnant patient. Patients are without any signs of disease 42, 20, and 17 months after surgery. CONCLUSION: This tumor is a distinctive and rare translocation carcinoma of the kidney [t(6;11), HMB45 positive]. All cases with known clinical data arose in younger people. The malignant potential is probably low.
Keywords: dospělí; nádory ledvin; těhotenství; Humans; Carcinoma, Renal Cell; Kidney Neoplasms; Antigens, Neoplasm; Neoplasm Proteins; Melanoma-Specific Antigens; karcinom z renálních buněk; mladý dospělý; melanomové antigeny; mužské pohlaví; nádorové komplikace v těhotenství; Translocation, Genetic; Adult; nádorové proteiny; antigeny nádorové; Pregnancy Complications, Neoplastic; ženské pohlaví; translokace genetická; lidé; Pregnancy; Male; Young Adult; Female